KEMAMPUAN MANAJERIAL KYAI DALAM MENGELOLA PONDOK PESANTREN AL-ITTIFAQ - Sri Widaningsih (STKIP Pesisir Selatan, 2023)
The important management of Islamic boarding schools is very helpful in achieving educational goals in Islamic boarding schools. The purpose of this study is to describe and analyze the managerial abilities of Kyai in the process of managing Islamic boarding schools. This study uses a qualitative method with a